The Investigation on Criminal Acts of Corruption in the Jurisdiction of Rembang Police - Angga Dwi Arifian; Sri Kusriyah (Law Development Journal, 2021)
This study aims to identify and analyze the investigation of criminal acts of corruption in the Rembang Police Legal Area and the obstacles in investigating corruption crimes in the Rembang Pores jurisdiction and their solutions. The approach method used is sociological juridical, descriptive analytical research specifications, types and sources of data using primary and secondary data, data collection methods are field studies and literature studies, while the data analysis method uses qualitative analysis. The results showed that the investigation of criminal acts of corruption in the jurisdiction of the Rembang Police was carried out in accordance with the provisions of the Criminal Procedure Code through several stages, namely collecting evidence, determining the suspect, examining witnesses and suspects and finally submitting the investigation file, suspects and evidence to the public prosecutor. In the investigation process there are several obstacles faced, namely the length of the process of collecting evidence, the suspect providing convoluted information, returning the case file by the public prosecutor.